Cooperative resource sharing for multi rate cognitive networks - Yan ZHANG; Min SHENG; Jian-dong LI; Wei-jia HAN; Xiao MA (Tongxin xuebao)
The motivations and strategies of cooperation between heterogeneous networks were discussed for multi rate cognitive networks.Based on queuing theory,the delay analytical models for different cooperative strategies were proposed and the closed form analysis,which exactly shows the relationship among different users’ traffic arrival rate,packet length,transmission rate and service delay,was obtained to reveal the delay performance and appropriate application scenarios of different cooperative strategies.The simulation results confirm that the proposed analytical model is correct and effective.In addition,it shows that not only the QoS of primary user is better guaranteed,but also the access opportunity and QoS of secondary user are improved by cooperation dramatically.